2021
DOI: 10.1177/0145561321989143
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Prostheses in Endoscopic Transcanal Stapes Surgery for Otosclerosis Cases

Abstract: Objectives: Hydroxyapatite is a commonly used material for medical applications due to its excellent biocompatibility. We use hydroxyapatite prosthesis for the reconstruction of the ossicular chain in stapes surgery. In this study, we report a case series of endoscopic ear surgery using a basket-type hydroxyapatite prosthesis. Methods: We retrospectively examined 8 cases of endoscopic transcanal stapes surgery using hydroxyapatite prostheses. We evaluated the postoperative results and complications. Results: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Postoperative complications after stapes surgery vary from sensorineural hearing loss (SNHL) and dizziness to dysgeusia due to injury to the chorda tympani. Postoperative 10 reported the highest rate, of 66.67%, followed by Hosoya et al 17 (50%), while Gulsen and Karatas 14 reported the lowest rate: 2.63%. Dursun et al 9 and Naik and Nemade 16 did not report cases of postoperative dizziness.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…Postoperative complications after stapes surgery vary from sensorineural hearing loss (SNHL) and dizziness to dysgeusia due to injury to the chorda tympani. Postoperative 10 reported the highest rate, of 66.67%, followed by Hosoya et al 17 (50%), while Gulsen and Karatas 14 reported the lowest rate: 2.63%. Dursun et al 9 and Naik and Nemade 16 did not report cases of postoperative dizziness.…”
Section: Discussionmentioning
confidence: 86%
“…Regarding transient postoperative dizziness, the overall rate was of 8.4% (range: 2.63% to 66.67%) cases. Marchioni et al 10 reported the highest rate, of 66.67%, followed by Hosoya et al 17 (50%), while Gulsen and Karatas 14 reported the lowest rate: 2.63%. Dursun et al 9 and Naik and Nemade 16 did not report cases of postoperative dizziness.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations